Multilingual Mastery Implementation Management in the M3 School Program: Language Learning Strategies - Nika Fellisiana Putri; Choirun Nisa (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study was motivated by the need for multilingual education in the era of globalization, which requires proficiency in various languages as a 21st-century competency. Purpose is to identify the program’s implementation management, the language learning strategies employed, and the supporting and hindering factors in its execution. The location of this research is at SD Muhammadiyah 3 Pekajangan, Pekalongan. Methodology: This study employs a qualitative narrative approach through interviews, observation, and documentation.Results: The M3 (Mutip Multilingual Mastery) program is implemented through the stages of planning, organizing, implementation, and monitoring and evaluation, involving teachers, homeroom teachers, and school principals. Learning still focuses on memorization and vocabulary repetition. Supporting factors include student motivation, teacher consistency, school facilities, and parental support, while obstacles include time constraints, low interest, difficulty in understanding foreign languages, and a lack of variety in methods and media. The M3 (Mutip Multilingual Mastery) program is running quite well, but it still requires learning innovations to optimize its results.Applications/Originality/Value: This study provides an effective management model for the Mutip Multilingual Mastery (M3) program that can be applied in other schools to improve the quality of multilingual learning implementation.